2019
DOI: 10.1108/apjml-08-2018-0334
|View full text |Cite
|
Sign up to set email alerts
|

Determining factors of tourists’ loyalty to beach tourism destinations: a structural model

Abstract: Purpose The purpose of this paper is to investigate and develop an integrated theoretical relationship by including destination image and attitudes into the quality-value-satisfaction-loyalty paradigm in the context of beach tourism. Design/methodology/approach A personal-administered survey was conducted using a convenient sampling technique to collect data from 601 tourists who had visited popular beach destinations in Bangladesh. Then, the structural relationships between the factors likely to affect tour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 81 publications
4
33
1
3
Order By: Relevance
“…It is an important principle that plays a role in a tourist's choices. The destination image is considered to be a key aspect of tourist decisionmaking [9][10][11][21][22][23]. The impact of tourism on countries and local destination economic growth has been widely confirmed [24][25][26] and boost the competition between countries in the tourism industry [27,28].…”
Section: Destination Imagementioning
confidence: 99%
See 2 more Smart Citations
“…It is an important principle that plays a role in a tourist's choices. The destination image is considered to be a key aspect of tourist decisionmaking [9][10][11][21][22][23]. The impact of tourism on countries and local destination economic growth has been widely confirmed [24][25][26] and boost the competition between countries in the tourism industry [27,28].…”
Section: Destination Imagementioning
confidence: 99%
“…As a significant determinant of tourist behavior, motivation has been widely researched by academics since the 1940s. At the same time, some researchers have tried to examine their relationships with other constructs, such as destination image [44,45], destination loyalty [8,10,11,13,14]. Since the beginning of these areas of study, motivation has been an important subject in leisure and tourism literature review [46,47].…”
Section: Tourist Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…All these mainstream literatures indicate the perceived value as antecedent of satisfaction and loyalty. Perceived value is also found to have direct effect on destination image, tourist attitudes and satisfaction and additionally destination image and satisfaction significantly affected tourist attitudes and loyalty (Hasan, Abdullah, Lew, & Islam, 2019).For instance, the empirical evidences show the existence of the chain of constructs, service quality-perceived value-customer satisfaction-loyalty in a service setting (Gallarza, Saura, & Moreno, 2013). Sun et al (2013) reported that perceived value for the past two decades had received great attention from the marketing researchers due its significance as a factor that enables better understanding of consumer behavior and loyalty behavior.…”
Section: Perceived Valuementioning
confidence: 89%
“…A strong DNI can naturally create a decisive advantage in safeguarding destination loyalty in post COVID-19 tourism (Chaulagain et al, 2019;Gössling et al, 2020;Zenker & Kock, 2020). The destination loyalty concept has been attracting tourism researchers' interest for the last decades with a special focus given to its conceptualization (Prayag & Ryan, 2012) and antecedents (Lindblom et al, 2018;Hasan et al, 2020. Although destination loyalty has frequently been conceptualized with attitudinal and behavioral loyalty dimensions (Kumar et al, 2020;Liu et al, 2019), behavioral loyalty has been criticized due to only focusing on the actual outcome of tourist's decision-making process while overlooking tourist intentions and motives (Yoon & Uysal, 2005).…”
Section: Dni and Edly Under Covid-19mentioning
confidence: 99%